A new species of Hyalella (Crustacea, Amphipoda, Dogielinotidae) from the Atlantic forest of Misiones, Argentina - Colla, María Florencia (2015)
The freshwater genus Hyalella Smith, 1874 has a distribution restricted to the Western Hemisphere with most species being found in South America. In this report we describe a new species of Hyalella from the Atlantic Forest of the Misiones province, Argentina.